Characterization of the acetylation of cyclooxygenase-isozymes and targeted lipidomics of eicosanoids in serum and colon cancer cells by the new aspirin formulation IP1867B versus aspirin in vitro - Hofling, Ulrika; Tacconelli, Stefania; Contursi, Annalisa; Bruno, Annalisa; Mucci, Matteo; Ballerini, Patrizia; Cohen, Simon; Patrignani, Paola (Frontiers in Pharmacology, 2022)
Background. Aspirin(acetylsalicylic acid, ASA) is recommended for the secondary prevention of atherothrombotic events and has shown anticancer effects. The current enteric-coated drug formulation may reduce aspirin bioavailability. Liquid formulations could improve aspirin pharmacokinetics and pharmacodynamics. IP1867B is a liquid-aspirin formulation that combines three ingredients, ASA/triacetin/saccharin. Methods. ASA and IP1867B(L-ASA) were assessed in human serum(obtained by allowing to clot human whole blood at 37°C for 1h), washed platelets, and colonic adenocarcinoma HCA7 cells on eicosanoid generation and COX-isozyme acetylation at Serine529 and 516 by LC-MS/MS. Results. In serum, ASA and L-ASA acted by selectively affecting COX-1-derived eicosanoids, including thromboxane(TX)B2. L-ASA was more potent in inhibiting serum TXB2, a known biomarker of aspirin antiplatelet effect, than ASA. However, ASA and L-ASA were equipotent to acetylate COX-1 in washed platelets and COX-2 in HCA-7 cells. In HCA-7 cells, ASA and L-ASA acted by inhibiting prostaglandin(PG)E2(the most abundant prostanoid) and TXB2 biosynthesis. In the presence of a high arachidonic acid concentration(100 microM), 15R-hydroxyeicosatetraenoic acid(HETE) was generated at baseline by cancer cell COX-2 and was only slightly enhanced by supratherapeutic concentrations of ASA(1mM). In whole blood and HCA7 cells treated with ASA or L-ASA, 15-epi-lipoxin(LX)A4 were undetectable. Conclusions. IP1867B was more potent in affecting serum TXB2 generation than ASA. The relevance of this finding deserves evaluation in vivo in humans. In cancer cells, ASA and IP1867B acted by inhibiting PGE2 and TXB2 generation via the acetylation of COX-2. ASA and IP1867B at clinically relevant concentrations did not substantially induce the biosynthesis of 15R-HETE and 15-epi-LXA4.